First record of preserved soft parts in a Palaeozoic podocopid (Metacopina) ostracod, Cytherellina submagna: phylogenetic implications - Olempska, E. (The Royal Society, 2012)
The metacopines represent one of the oldest and most important extinct groups of ostracods, with a fossil record from the Mid-Ordovician to the Early Jurassic. Herein, we report the discovery of a representative of the group with three-dimensionally preserved soft parts. The specimen—a male of Cytherellina submagna—was found in the Early Devonian (416 Ma) of Podolia, Ukraine. A branchial plate (Bp) of the cephalic maxillula (Mx), a pair of thoracic appendages (walking legs), a presumed furca (Fu) and a copulatory organ are preserved. The material also includes phosphatized steinkerns with exceptionally preserved marginal pore canals and muscle scars. The morphology of the preserved limbs and valves of C. submagna suggests its relationship with extant Podocopida, particularly with the superfamilies Darwinuloidea and Sigillioidea, which have many similar characteristic features, including a large Bp on the Mx, the morphology of walking legs, Fu with two terminal claws, internal stop-teeth in the left valve, adductor muscle scar pattern, and a very narrow fused zone along the anterior and posterior margins. More precise determination of affinities will depend on the soft-part morphology of the cephalic segment, which has not been revealed in the present material.